Analyzing the Vulnerability in Open Source Software - Singh, Madanjit; Saini, Munish; Kaur, Manevpreet (International Journal of Computer Sciences and Engineering, 2019)
Secure code is one of the key parameters which must be taken care while software is being developed. Inspecting the source code at the earlier stages is always a better approach. Inspection involves carefully examining the source code for any flaws which may cause problems in the later stage of the software life cycle. The Vulnerability is a kind of weakness or security flaws in code that can be exploited by an attacker to perform unauthorized actions. A vulnerable code will lead to severe threats to the security of software. In this paper, we have investigated the source code of a well-known open source software (OSS) projects written in C and C++ programming language and figure out the presence of vulnerability in the software. The results also indicate that the vulnerabilities in the source code have shown an increasing trend with the lines of code (LOC). It pointed to the fact that addition of new features or change request into the OSS project will cause an increase in the vulnerability as well. It gives significant implication to the developers or project managers of OSS projects to not deny the existence of security flaws in the software as the software evolves. The obtained results will also help the project managers and developers to measure the state of software.